STRATEGI KEPALA SEKOLAH MADRASAH ALIYAH AR-RAHMAH DALAM MENARIK MINAT CALON SISWA BARU - Diah Puspita Loka; Mahpus Mahpus; Wandi Syahindra; Asri Karolina (PAI RAFAH, 2020)
Since the last few years, Islamic Senior High School (Madrasah Aliyah) Ar-Rahmah Rejang Lebong has experienced a decline in student interest. Regarding this problem, the principal tried to do a promotion strategy. In this research, the researcher found some aspects of the strategy that the principal did, namely advertising trough brochures and banners, direct marketing, interactive or internet marketing, sales promotion, and even publicity or public relations. In carrying out these strategies, there are some obstacles faced by the school, such as competition with other Islamic and public schools and the inadequate facilities of Madrasah Aliyah infrastructure that reduce students’ interest in this school.This research applied a qualitative approach. The subjects of this research were the Principal of Madrasah Aliyah Ar-Rahmah, the education staff involved in the learning process, the students as objects and subjects of learning as well as the surrounding community. The data were collected by using observation, interviews, and documentation. In analyzing the qualitative data, the researcher used data analysis techniques by Miles and Huberman model that includes some aspects namely Data Reduction, Data Presentation, and Drawing Conclusions.The result of this research revealed that the principal’s strategies to attract students’ interest at Madrasah Aliyah Ar-Rahmah have been good. However, there are some obstacles as regards other schools as the competitor and a limitation of school facilities. Therefore, the increase of prospective students’ interest cannot be ensured every year.